1999
DOI: 10.1089/15204559950019988
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic Activation of Porcine Oocytes After Nuclear Transfer

Abstract: Mature porcine oocytes are arrested at metaphase II of meiosis. At fertilization, like all mammalian oocytes they exhibit a low frequency Ca(2+) oscillation lasting several hours. This oscillation is thought to be the signal that triggers resumption of meiosis and activates the developmental program of the oocyte. The signal transduction mechanism of the sperm-induced Ca(2+) signal is not known in detail, and attempts to generate the oscillation artificially have met with little success. Nevertheless, artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…1993). On the other hand, parthenogenetic activation can be induced through the elevation of cytoplasmic free calcium by several methods (see review by Machaty et al. 1999).…”
Section: Factors Affecting Developmental Ability Of Icsi Produced Embmentioning
confidence: 99%
See 1 more Smart Citation
“…1993). On the other hand, parthenogenetic activation can be induced through the elevation of cytoplasmic free calcium by several methods (see review by Machaty et al. 1999).…”
Section: Factors Affecting Developmental Ability Of Icsi Produced Embmentioning
confidence: 99%
“…The primary role of the fertilization calcium signal is to downregulate the activity of the cell cycle regulatory MPF that leads to exit from the metaphase arrest (Lorca et al 1993). On the other hand, parthenogenetic activation can be induced through the elevation of cytoplasmic free calcium by several methods (see review by Machaty et al 1999). Even, spontaneous activation by in vitro oocyte ageing can be performed (Kikuchi et al 1995).…”
Section: Icsi Technical Factors and Further Embryo Developmentmentioning
confidence: 99%
“…Activation methods in the pig have been reviewed recently by Machaty, et al (1999). Most activating treatments affect a broad spectrum of cellular components; in addition to the activating effect, physiology of the oocyte may be altered in various ways.…”
Section: Introduction P Arth Eno Gen Esis Has Been a Pow Er Fu L Methmentioning
confidence: 99%
“…The HHP treatment did not cause parthenogenetic activation in the studies when TCMH medium was used to hold oocytes during treatment. As various physical (mechanical, electronic, osmotic), chemical and other treatments (Machaty and Prather 1998; Machaty et al. 1999; Somfai et al.…”
Section: Hydrostatic Pressure Treatment Of Oocytesmentioning
confidence: 99%
“…The HHP treatment did not cause parthenogenetic activation in the studies when TCMH medium was used to hold oocytes during treatment. As various physical (mechanical, electronic, osmotic), chemical and other treatments (Machaty and Prather 1998;Machaty et al 1999;Somfai et al 2007;Tian et al 2007) were reported to cause parthenogenetic activation, further experiments were conducted to investigate the effect of various holding media with different Ca 2+ concentrations on possible-HHP induced parthenogenetic activation of the oocytes. The media included TCMH medium, mannitol-PVA fusion medium with (MPVA+Ca 2+ ) or without Ca 2+ and Mg 2+ (MPVA).…”
Section: Treatment Mediamentioning
confidence: 99%